Mathematical Analysis of Diarrhea Model with Saturated Incidence Rate. - Musinguzi, Jason (Kabale University, 2024)
A compartmental mathematical model of (SITR)was presented to investigate the effect of saturation treatment on the dynamical spread of diarrhea in the community. The mathematical analysis shows that the disease-free and endemic equilibrium points of the model exist. The disease-free equilibrium is locally and globally asymptotically stable when RO< I and unstable otherwise RO> I.